Suggesting an Extensive Interpretation of the Concept of Novelty That Looks at the Bio-Cultural Dimension of Food - Poto, Margherita Paola; Morel, Mathilde (Sustainability, 2021)
“Novel food” in the European Union’s (EU) legal terms refers to any food that was not used for human consumption to a significant degree within the EU before 15 May 1997 (Regulation 2015/2283/EU (2015)). Placing novel food on the market requires a safety assessment when such novelty is ascertained, with the consequent need of an authorization procedure that is not required for food traditionally conceived in the EU. Studies have highlighted how such a Eurocentric proof of traditional/novel use of food results in unequal treatment of third countries, with a slowdown of their market investments in the EU market. This contribution addresses this aspect by critically examining the disparity of treatment and suggesting the adoption of a wide-ranging interpretation of food novelty that considers the biocultural context in which food is embedded. This work is based on a critical legal analysis through the hermeneutics of Reg. 2015/2283/EU (2015) and a case study on algae from Northern Norway and Sápmi, carried out by the project SECURE. We conclude that a legal interpretation connecting food to its biocultural context would contribute to qualify it as traditional and therefore facilitate its placement on the market. Our case study provides an example of the macroalgae collected in Northern Norway/Sápmi that through the criterion of the biocultural context would qualify as traditional food, without recourse to the authorization procedure. Further research could assess whether the European Commission’s list of authorized novel foods (which include algae whose status as novel food has been inquired and assessed) expands to also comprehend some of the low-trophic marine resources (LTMR) harvested in Northern Norway/Sápmi.